The Tissue-Selective Estrogen Complex (Bazedoxifene/Conjugated Estrogens) for the Treatment of Menopause - Lello, Stefano (Int J Endocrinol, 2017)
The tissue-selective estrogen complex (TSEC) pairs conjugated estrogens (CE) with a selective estrogen receptor modulator (SERM), bazedoxifene acetate (BZA). A 2-year treatment with the TSEC improved vasomotor symptoms, quality of life, and vaginal atrophy in healthy postmenopausal women. In addition, the TSEC prevented vertebral and hip bone loss without increasing mammographic density, breast tenderness, the risk of myocardial infarction, stroke, or venous thromboembolism. Finally, the BZA 20 mg/CE 0.45 mg dose did not increase the risk of endometrial hyperplasia. Based on these findings, the TSEC can be considered as a first-line treatment for symptomatic postmenopausal women.